Integrated physiological, metabolomic, and proteome analysis of Alpinia officinarum Hance essential oil inhibits the growth of Fusarium oxysporum of Panax notoginseng - Liu, Xiao-Yun; Huo, Ying-Ying; Yang, Jing; Li, Tian-Tian; Xu, Fu-Rong; Wan, He-Ping; Li, Jia-Nan; Wu, Chun-Hong; Zhang, Yong-Hong; Dong, Xian (Frontiers in Microbiology, 2022)
Abstract Fusarium oxysporum is the main pathogen of Panax notoginseng root rot, and chemical fungicides remain the primary measures to control the disease. Plant essential oil (EO) is a volatile plant secondary metabolic product that does not produce any residue to replace chemical pesticide. To comprehensively understand the antifungal mechanism of Alpinia officinarum Hance EO, the physiological indicators, proteome and metabolome were analyzed using F. oxysporum spores and hyphae treated with different EO concentrations. The cell membrane was damaged after both low and high concentrations of EO treatment, along with leakage of the cell contents. To resist the destruction of membrane structure, fungi can increase the function of steroid biosynthesis and expression of these catalytic enzymes, including squalene monooxygenase (SQLE), sterol 14alpha-demethylase (CYP51, CYP61A), delta14-sterol reductase (TM7SF2, ERG4), methylsterol monooxygenase (MESO1), and sterol 24-C-methyltransferase (SMT1). Furthermore, the tricarboxylic acid cycle (TCA) was influenced by inhibiting the expression of glutamate synthase (GLT1), 4-aminobutyrate aminotransferase (ABAT), and succinate-semialdehyde dehydrogenase (gabD); increasing malate and gamma-aminobutyric acid (GABA); and decreasing citrate content. The spore germination rate and mycelia growth were decreased because the expression of cohesin complex subunit SA-1/2 (IRR1) and cohesion complex subunit (YCS4, BRN1, YCG1) were inhibited. Particularly, under high EO concentrations, cyclin-dependent kinase (CDC28) and DNA replication licensing factor (MCM) were further inhibited to disrupt the cell cycle and meiosis, thus affecting cell division. The results of this study will enrich the understanding of the antifungal mechanism of EOs and provide an important basis to develop new plant-derived fungicides. Keywords: Essential oil; steroid biosynthesis; tricarboxylic acid cycle; cell cycle and meiosis; antifungal mechanism.